Introduksi Teknologi Budi Daya Hidroponik bagi Kelompok Calon Wirausaha di Masa Pandemi Covid-19 - Azhar Bafadal; Teguh Wijayanto; Surni Surni; Hadi Sudarmo; Zohorman Zohorman (Institut Pertanian Bogor, 2021)
The purpose of this activity is to provide knowledge and skills for prospective entrepreneurs affected by the Covid-19 Pandemic in qualified hydroponic cultivation techniques. The method of implementing the activity is in the form of indoor training on the concepts and techniques of hydroponic cultivation. In addition, outdoor technical guidance is also carried out regarding the construction of hydroponic installations and cultivation practices, starting from making nutrition, sowing seeds, planting to harvesting. The method of field visits to successful hydroponic entrepreneurs is also carried out. Participants can properly follow the training materials and technical guidance on assembling installations and practicing hydroponic cultivation. The benefits and level of satisfaction of participants in participating in this activity reached a score of 8.75. This activity increases the interest of the training participants for hydroponic entrepreneurship. The condition of the harvested plants has not yielded the expected results, with yields still around 50% of the achievable potential. To ensure the sustainability of the activity and have a wider impact, the Konda Village Party should facilitate so that the participants of this activity can become tutors for other people who want to do hydroponic entrepreneurship.